REBAMIPIDE: EFFECTIVE DRUG IN THE PREVENTION OF NSAID GASTROPATHY - Sotliqov Rashid Karimovich,; Tangirov Tangribergan Azadovich, (EPRA International Journal of Multidisciplinary Research (IJMR), 2022)
Prevention of the development of complications from the gastrointestinal tract (GIT) is the most important element of the rational use of non-steroidal anti-inflammatory drugs (NSAIDs). For a long time, proton pump inhibitors (PPIs) were the only means of drug prevention of these complications. However, PPIs are effective only for the prevention and treatment of pathology of the upper gastrointestinal tract (NSAID-gastropathy). Today, Uzbek doctors have a new tool for protecting the gastrointestinal mucosa - rebamipide. The action of this drug is different from that of PPIs: it is a typical gastro- and enteroprotector that enhances the synthesis of endogenous prostaglandins and has a significant anti-inflammatory potential. The drug has long been widely used by doctors in Japan, South Korea and China as an effective and safe remedy for the treatment of many diseases of the digestive system. There is a strong evidence base confirming the effectiveness of rebamipide for the prevention and treatment of NSAID gastropathy. According to controlled studies, it is not inferior to the "classic" gastroprotector misoprostol, significantly surpassing the latter in terms of tolerability. This review presents the mechanism of action of rebamipide and presents the main clinical studies that have studied its therapeutic effect in NSAID gastropathy.